Developing of Evaluation Criterions for Graduation Projects in Interior Design Specialization - OCMT as A Case Study (Journal of University of Babylon for Engineering Sciences, 2018)
In the academic institutions, Graduation project is subject to judging and evaluation by a specialized academic committee, based on evaluation criterion extract from the specialization, technical and skill topics, which studied by the student and implemented it in the project theoretically and practically.These criterion are not fixed, so we choose the evaluation criteria which are applied in interior design department at Oman College for Management & Technology (OCMT)  as a case study, starting with identify syllabus of graduation project course, according to the study plan of department, then moving towards suggestions and thoughts for changing and developing current criterion, or adding new criterion for keep up with new and modern subjects related to all specializations, then conduct descriptive, relative and value comparisons between criteria before and after development, aiming to indicate the most comprehensive criterion for  project evaluation.In conclusion, highlighting positive points in the projects, and emphasizing on negatives points to avoid in the practical life, and encourage student to view the projects and ideas proposed by governmental institutions for the graduation project in accordance with the local community, heritage and identity, to access the graduation projects depended on developing study plan, that will help student to be in a high level and qualify him to supply the labor market nationally and regionally.